This gets to the foundations of algebra, needing to add or subtract the same value from both sides, then getting all the x terms on one and all the numbers on the other.
PROBLEM 1:
5x - 6 = 4x + 2
You want the x terms all on one side, so subtract 4x from both sides:
5x - 6 - 4x = 4x - 4x + 2
This simplifies to:
5x - 4x - 6 = 2
Then you have 5x - 4x ---> this is 1x which is the same as just x.
x - 6 = 2
Finally, add 6 to both sides:
x - 6 + 6 = 2 + 6
x = 8
Now it is always a good idea to check your answer by plugging it back into the original equation to see if it works:
5x - 6 = 4x + 2
5(8) - 6 = 4(8) + 2
40 - 6 = 32 + 2
34 = 34 <-- check
So the correct answer to Problem 1 is x = 8.
Remember at each step, to cancel something from one side, you need to do the opposite operation. So if you have +4x, you need to subtract 4x from both sides. If you have -6, you have to add 6 to both sides.
PROBLEM 2:
12x - 6 = 11x
Again subtract the 11x from both sides (to cancel 11x from the right):
12x - 11x - 6 = 0
x - 6 = 0
Add 6 to both sides (to cancel -6 from the left):
x -6 + 6 = 6
x = 6
As a double check:
12x - 6 = 11x
12(6) - 6 = 11(6)
72 - 6 = 66
66 = 66 <-- check
So the answer to Problem 2 is x = 6
2006-12-08 10:28:50
·
answer #1
·
answered by Puzzling 7
·
0⤊
0⤋
OK, (We have to find the value of x)
So we have to put x on one side of the " = " and the number on the other side. To do this we have to rearrange the equation. A handy thing i use in these circumstances is the "change side, change sign" for example your first problem.
1.) 5x - 6 = 4x + 2
2.) 5x = 4x + 2 +6
3.) 5x = 4x + 8
4.) 5x - 4x = 8
5.) x = 8
See in line 2 how i moved the - 6 over to the other side and changed its sign from a negative to a positive? This is what a mean by "change side, change sign." In the next step i merely added the like "like terms" together - (2 + 6 =8) Then I changed the 4x over to the other side and added the like terms together again. But, beware because i changed the side of the term the sign changed and adding the like terms together is in fact subtracting them > 5x - 4x = 1x (or more correctly just x)
See if you can do the next one now use the change side, change sign thing.
I hope that helps you, if you want more help with those just email me.
2006-12-08 18:47:41
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
5x-6=4x+2
first we had -6 to each side
5x=4x+2+6 which equals 5x=4x+8
next we subract 4x from each side
5x-4x=8 which equals 1x=8
we would now divide each side by 1, but is not really needed because 8/1=8. so x=8
problem number 2 is the same:
12x-6=11x
12x=11x+6
12x-11x=6
x=6
2006-12-08 19:11:50
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
5x-6=4x+2 (add 6 to the right side)
+6 +6
5x= 4x+8 (subtract 4x from the right side)
-4x=-4x
1x/1=8/1 (divide)
x=8
12x-6=11x (add 6 to the right side)
+6= +6
12x= 11x+6 (subtract 11x from the right side)
-11x=-11x
1x/1=6/1 (divide)
x=6
I think this is right, hope it helps.
2006-12-08 18:45:28
·
answer #4
·
answered by libra20 2
·
0⤊
0⤋
1) 5x -6=4x+2
+6 +6
5x = 4x + 8
-4x -4x
x=8
2) 12x-6=11x
-11x -11x
x-6=0
+6 +6
x=6
Remember to isolate the variables!!!
2006-12-08 18:35:16
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
1) 5x -6=4x+2
5x - 4x = 2 + 6
x = 8
2) 12x-6=11x
12x - 11x = 6
x = 6
>>`´<<
2006-12-08 18:41:58
·
answer #6
·
answered by aeiou 7
·
0⤊
0⤋
First you have to get all the x items on the same side of the equation. Whatever you do to one side of the equation you can do to the other side. (Whatever happens on one side of = must be the same on the other side.)
5x-6=4x+2
You can start by subtracting 4x from each side. That would look like this:
5x-6-4x=4x+2-4x
Now since 4x-4x is 0, you have 5x-6-4x=2.
Do the same thing to get 6 to the other side of =.
5x-4x-6+6=2+6
Make sense? Then all you have left to do is subtract 4x from 5x and you have the answer.
2006-12-08 18:33:22
·
answer #7
·
answered by C 1
·
0⤊
0⤋
1)
5x -6=4x+2
5x-4x=2+6
x = 8
2)
12x-6=11x
12x-11x = 6
x = 6
₢
2006-12-08 21:43:11
·
answer #8
·
answered by Luiz S 7
·
0⤊
0⤋
1.5x-6=4x+2
-4x -4x
1x-6=2
+6 +6
1x = 8
/1 /1
x=8
2. 12x-6=11x
-12x -12x
-6= -1x
/-1 /-1
6=x
2006-12-08 18:33:02
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
1) 5x -6=4x+2 subtract 4x from each side
x-6=2 add 6 to each side
x=8
2) 12x-6=11x subtract 12x from each side
-6=-x multiply each side by -1
x=6
2006-12-08 22:27:50
·
answer #10
·
answered by yupchagee 7
·
0⤊
0⤋